Topological Classification of Conformal Actions on pq-Hyperelliptic Riemann Surfaces - Ewa Tyszkowska (International Journal of Mathematics and Mathematical Sciences)
A compact Riemann surface X of genus g>1 is said to be p-hyperelliptic if X admits a conformal involution ρ, for which X/ρ is an orbifold of genus p. If in addition X is q-hyperelliptic, then we say that X is pq-hyperelliptic. Here we study conformal actions on pq-hyperelliptic Riemann surfaces with central p- and q-hyperelliptic involutions.